On the regularity criterion for the 2D Boussinesq equations involving the temperature. Issue 3 (3rd March 2016) - Ye, Zhuan
Abstract : In this paper, we establish a regularity criterion in terms of the temperature for the 2D fractional Boussinesq equations with zero heat conductivity.